The Influence of Organizational Culture, and Work Motivation on Work Discipline Employees in Secretariat General of the National Resillience Council - Afanti Side Uloli; Maruf Akbar; Kadir Kadir (Journal of International Conference Proceedings (JICP), 2019)
Employees at The National Resillience Council General Secretariat experienced problems related to work discipline. The purpose of this study was to determine the effect of organizational culture and work discipline on work motivation employees. This study used 115 employees in secretariat general of the national defence council. The results show that organizational culture has a significant and positive effect on work motivation. Work discipline also has a significant and positive effect on work motivation. The implications of this study indicate that to be able to improve work motivation, high work discipline and high organizational culture are needed. Employees need the encouragement of superiors to have the desire to be present at work.